Podstawy metodologiczne dydaktyki literatury w ujęciu historycznym = Methodological principles of literary didactics in a historical aspect - Krauze, Urszula (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The subject of this paper is the analysis of theoretical conditions of opinions and cogitations on knowledge and teaching literature in Polish schools beginning from the half of the nineteenth century. The authoress investigates the evolution of standpoints and opinions under the principle of the choice of contents and ways of teaching literature, which occured and still occure in the consciousness of theorists and practicians of teaching under the influence of research-tendencies within the science of literature and within pedagogical sciences in the course of the century.
Keywords: dydaktyka literatury; metodologia